Enhancement of a SWIPT Based Amplify and Forward Cooperative Relaying Protocol for Wireless Communication System - Ojo, Festus Kehinde; Akintoye, Nafiu Olayiwola; Ojo, Samson Iyanda; Oyedokun, Oluwatobi Omolola (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Communication through unbounded environment known as Wireless Communication (WC) undergoing rapid expansion driven by the escalating demand for its services. However, WC system is subjected to severe multipath propagation due to obstruction in the medium of transmission thereby resulting in signal fading that degrades system performance. SWIPT based Amplify and Forward (AF) relaying protocol previously used in addressing signal fading is characterized with poor performance due to noise amplification. Hence, this paper, enhanced a SWIPT based AF relaying technique for WC system using angular beamforming at the source and spectral subtraction at the relay node. The transmitting signal at the source was beamformed using angular beamforming technique at varying angles of and . The received signal was made to pass through Power Splitter (PS) energy harvester where the signal power was splited into two fractions, and . The first fraction that is , was used for energy harvesting by making it to pass through energy harvester device to scavenge energy and store in the power storage. The remaining fraction that is, , was made to pass through spectral subtraction and amplify using relay gain before forwarded to the destination during second hop transmission. The enhanced technique’s performance was assessed using BER and TP, comparing it to the existing SWIPT-based AF relaying technique. The enhanced SWIPT based AF gave better performance with reduce BER and improve TP which justify the reduction of amplify noise in the propose technique. The proposed technique can be integrated into wireless communication systems to improve their overall performance.